Clean Label Approaches in Cheese Production: Where Are We? - Jaime Fernandes; Sandra Gomes; Fernando H. Reboredo; Manuela E. Pintado; Olga Amaral; João Dias; Nuno Alvarenga (Foods)
The Clean Label concept has gained significant traction in the cheese industry due to consumer preferences for minimally processed cheeses free from synthetic additives. This review explores different approaches for applying Clean Label principles to the cheese industry while maintaining food safety, sensory quality, and shelf life. Non-thermal technologies, such as high-pressure processing (HPP), pulsed electric fields (PEF), ultra-violet (UV), and visible light (VL), are among the most promising methods that effectively control microbial growth while preserving the nutritional and functional properties of cheese. Protective cultures, postbiotics, and bacteriophages represent microbiological strategies that are natural alternatives to conventional preservatives. Another efficient approach involves plant extracts, which contribute to microbial control, and enhance cheese functionality and potential health benefits. Edible coatings, either alone or combined with other methods, also show promising applications. Despite these advantages, several challenges persist: higher costs of production and technical limitations, possible shorter shelf-life, and regulatory challenges, such as the absence of standardized Clean Label definitions and compliance complexities. Further research is needed to develop and refine Clean Label formulations, especially regarding bioactive peptides, sustainable packaging, and advanced microbial control techniques. Addressing these challenges will be essential for expanding Clean Label cheese availability while ensuring product quality and maintaining consumer acceptance.